Wenshen-Jianpi prescription, a Chinese herbal medicine, improves visceral hypersensitivity in a rat model of IBS-D by regulating the MEK/ERK signal pathway - Jiang, Tianyuan; Niu, Ran; Liu, Qian; Fu, Yuhan; Luo, Xiaoying; Zhang, Tao; Wu, Baoqi; Han, Juan; Yang, Yang; Su, Xiaolan; Chen, Jiande D. Z.; Song, Gengqing; et al. (Frontiers in Pharmacology, 2022)
The study is aimed to analysis the mechanism of WJP in alleviate the visceral hypersensitivity in IBS-D model rats. In this study, 36 SD rats aged 4 weeks were randomly divided into model group (n=27) and control group (n=9). The rat model of IBS-D was established by modified compound methods, for 4 weeks. After the modeling, they were randomly divided into three groups, including IBS-D model group (n=9), the positive drug group (n=9) and the WJP group (n=9), with different interventions. AWR were observed to evaluate the visceral sensitivity, and detection of the expression of TNF-α and histopathological examinations were performed to evaluate the inflammation in the colon of IBS-D model rats, and the key factors of MEK/ERK signal pathway in the tissue of colon and hippocampus were detected. Compared with the control group, the score of AWR in the model group at each pressure level were significantly increased (P=0.0003, P < 0.0001, P=0.0007, P=0.0009). And that in the WJP group were significantly decreased (P=0.0003, P=0.0007, P=0.0007, P=0.0009). Compared with the control group, the expression of TNF-α in the colon tissue in model group were significantly increased (P<0.0001), those in the WJP group were significantly decreased (P<0.0001). Compared with the control group, the expression of p-MEK1/2, p-ERK1 and p-ERK2 in the colon tissue were significantly increased in the model group (P<0.0001). Those in the colon tissue were significantly decreased in the WJP group (P＜0.0001). Compared with the control group, the expression of p-MEK1/2, p-ERK1 and p-ERK2 in the hippocampus tissue were significantly increased in the model group (P<0.0001). Those in the colon tissue were significantly decreased in the WJP group (P =0.0089, P =0.0387, P=0.0443). The results indicated that WJP can alleviate the visceral hypersensitivity in IBS-D model rats, mainly accompanied by down regulating the expression of TNF-α, p-MEK1/2, p-ERK1 and p-ERK2 in the colon tissue. And limited effect on down regulating the key parameters in the hippocampus tissue.